FAKTOR-FAKTOR YANG MEMPENGARUHI TUNDA JUAL GABAH DI DESA SEGEROYOSO KECAMATAN PLERET KABUPATEN BANTUL - Wulandari Dwi Etika Rini (Jurnal Dinamika Sosial Ekonomi, 2007)
The research aim to know the factors afected of rice sale delay rice farmers in Segoroyoso Village, District of pleret, Bantul Regancy. The research method used survey. The reseacrh location is determined by purposive method and intake of responder in sesus. Primary data were collected by interviewing with rice farmers in Segoroyoso village in December 2006. The data were analyzed by multiple linier regression model. The research result show that the factors affected of sale delay is area of the field, the others income and household consumption.Keywords: rice, sale delay